SKRINING BAKTERI PENDEGRADASI POLIETILEN DARI TEMPAT PEMBUANGAN AKHIR (TPA) MUARA FAJAR PEKANBARU SEBAGAI RANCANGAN HANDOUT PADA MATERI BACTERIA KELAS X SMA - Ridho Safna; Irda Sayuti; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to explore bacteria that can degrade polyethylene from the Muara Fajar Pekanbaru landfill site to produce Bacteria material handouts in class X high school. The study was conducted at the Sumatra Biota Laboratory of Andalas University and the Microbiology Laboratory of the Faculty of Medicine, Riau University. Fajar Pekanbaru. The research took place in December 2017-May 2018. The research consisted of two stages, namely the screening stage of polyethylene degrading bacteria from the TPA Muara Fajar Pekanbaru landfill and the handout design stage. The stage of field data collection is carried out by exploratory research, data collection by experimental methods, determination of sampling points by purposive sampling. The parameters in the study are the types of isolates of polyethylene degrading bacteria and their level of degradation. The results obtained by 4 isolates of polyethylene degrading bacteria were coded BTS-1 (Bacillus sp 1) BTS-2 (Bacillus sp 2) BTS-3 (Klabsiella sp) and BTS-4 (Pseudomonas sp). BTS-4 bacterial isolates had the highest degradation ability to degrade plastics by 10%, while the lowest bacterial isolates in polyethylene degradation were BTS-3 with a degradation rate of 1.9%. Based on an analysis of the potential results of the research, a handout of waste material and waste management for Biology learning in class X was designed.Key Words: Bacteria, Handout, Polyethylane